Impact of Male Partner Involvement on Women’s Adherence to the Dapivirine Vaginal Ring During a Phase III HIV Prevention Trial - Roberts, Sarah T.; Nair, Gonasagrie; Baeten, Jared M.; Palanee‑Philips, Thesla; Schwartz, Katie; Reddy, Krishnaveni; Kabwigu, Samuel; Matovu Kiweewa, Flavia; Govender, Vaneshree; Gaffoor, Zakir; Singh, Nishanta; Siva, Samantha; et al. (AIDS and Behavior, 2020)
identified as one of the most significant factors impacting women’s willingness and ability to use them. As a result, research teams have sought to increase male partner involvement by encouraging disclosure of product use to male partners, promoting male partner engagement in the study through attendance at the study clinic, and helping women to garner male partner support for product use. This paper aims to assess the impact of these three elements of male partner involvement on women’s adherence to the dapivirine vaginal ring during MTN-020/ASPIRE, a phase III randomized placebo-controlled clinical trial involving 2629 women in Malawi, South Africa, Uganda, and Zimbabwe. During the study, 64–80% of participants reported disclosure of ring use at each quarterly visit, and 13% reported that their partners had attended the study clinic at some point during the study. At study exit, 66% reported that their partner was supportive, 18% unsupportive, and 17% were unsure. After adjusting for age, site and time in study, women were more likely to have low ring adherence if they had an unsupportive male partner (aRR 1.29, 95% CI 1.03–1.62). Neither disclosure nor clinic attendance directly predicted ring adherence, but disclosure increased the probability of having a supportive partner (aRRR 24.17, 95% CI 16.38–35.66) or an unsupportive partner (aRRR 4.10, 95% CI 2.70–6.24), relative to an unknown level of partner support. Women were also more likely to have a supportive partner if their partner had attended the clinic (aRRR 3.77, 95% CI 1.36–10.42). This study suggests that although the vaginal ring is relatively discreet, lack of support from male partners remains a relevant barrier to use. Though both disclosure and clinic attendance may increase partner support, disclosure may also increase partner opposition. Interventions to reduce male partner opposition are needed to maximize the potential impact of the ring and other PrEP products for HIV prevention.
Keywords: HIV prevention; Women; Male involvement; Gender; Dapivirine vaginal ring